ANALISIS KAPASITAS SIMPANG DI SIMPANG KIAMBANG BATUSANGKAR KABUPATEN TANAH DATAR DENGAN METODE PKJI 2023 - Chika Islah Hani, Ripsyah; Yermadona, Helga; Endri, Endri (Ensiklopedia Research and Community Service Review, 2024)
Tanah Datar Regency is an area that is developing relatively rapidly, with social, economic, distribution and government activities. Apart from that, Tanah Datar Regency is quite popular with tourists every year. With the increase in population and the development of economic factors, social distribution and governance can have an impact on traffic problems. One of the intersections that is causing problems and congestion is the Kiambang intersection. This research aims to determine the performance of unsignalized intersections at Simpang Kiambang based on the PKJI 2023 method, the size of the intersection capacity and the level of intersection performance, the highest basic capacity obtained on Thustday 7 December 2023 was 1083 pcu/hour, the value of the degree of saturation (DJ) The highest value was obtained on Monday 11 December 2023 at 0.66, the highest delay (T) was found on Thursday 7 December 2023 at 19.53 sec/pcu, the highest queue probability (PA) value was obtained on Sunday 10 December 2023 around between 0.28% - 29.10%. Based on the results and discussion of the performance of the unsignalized intersection at Simpang Kiambang, it has a degree of saturation (DJ) of 0.66, indicating the level of service is at level C where traffic characteristics are stable, but vehicle speed and movement are controlled.Keywords: Performance of non-signalized intersections, PKJI 2023 method, Kiambang intersection,   degree of saturation, basic capacity.